2012
DOI: 10.1126/science.1222538
|View full text |Cite
|
Sign up to set email alerts
|

Cilia at the Node of Mouse Embryos Sense Fluid Flow for Left-Right Determination via Pkd2

Abstract: Unidirectional fluid flow plays an essential role in the breaking of left-right (L-R) symmetry in mouse embryos, but it has remained unclear how the flow is sensed by the embryo. We report that the Ca2+ channel Pkd2 is required specifically in the peri-nodal crown cells for sensing the nodal flow. Examination of mutant forms of Pkd2 shows that the ciliary localization of Pkd2 is essential for correct L-R patterning. Whereas Kif3a mutant embryos, which lack all cilia, failed to respond to an artificial flow, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
320
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(330 citation statements)
references
References 28 publications
8
320
0
2
Order By: Relevance
“…A link between ciliary Ca 2+ signaling, the polycystin proteins, and cyst development has recently gained attention (42,(46)(47)(48)(49)(50)(51). The fact that the cilia in the InsP3R3 and PC2 knockdown cysts were still present, but absent in InsP3R1 knockdown cysts, by week 8, suggests that cilia may not be essential to the latter stages of cystogenesis and is broadly consistent with recent findings (52).…”
Section: Discussionsupporting
confidence: 81%
“…A link between ciliary Ca 2+ signaling, the polycystin proteins, and cyst development has recently gained attention (42,(46)(47)(48)(49)(50)(51). The fact that the cilia in the InsP3R3 and PC2 knockdown cysts were still present, but absent in InsP3R1 knockdown cysts, by week 8, suggests that cilia may not be essential to the latter stages of cystogenesis and is broadly consistent with recent findings (52).…”
Section: Discussionsupporting
confidence: 81%
“…117 A third model suggests that the nodal flow initiates a Ca 2+ influx in crown cells on the left side of the node, via activation of the polycystins (PC2 and the PC1 homolog, PC1 like 1) in mechanosensory, immotile primary cilia. 7,9,118,119 In support of the latter model, the asymmetric expression of Ablim1 at the node during the mid-headfold stage requires both a nodal flow and PC2, but the details of this relationship have not been resolved. 114 Further, it was recently shown that glycosylation of the Notch receptor in the crown cells by the N-acetylgalactosamine-type O-glycosylation enzyme GALNT11 is essential for the optimal ratio between motile and immotile cilia at the mouse node, in addition to correct Pitx2 expression in Xenopus embryos.…”
Section: Nodal Cilia and Heterotaxymentioning
confidence: 99%
“…People with leftright situs inversus of the viscera are reported to have similar rates of left-lateralised language dominance to people with normally patterned viscera (Tanaka et al, 1999). Visceral asymmetry appears to arise as a consequence of the homochirality (biased handedness) of amino acid molecules in living systems, that together create 'handed' cilia leading to a unidirectional, leftward fluid flow within the embryonic node Takaoka, Yamamoto, & Hamada, 2007;Yoshiba et al, 2012), and ultimately to different gene expression cascades on the two sides of the body. Human CNS asymmetries may also arise from analogous molecular/biophysical asymmetries, but the core mechanism is unknown.…”
mentioning
confidence: 99%